Sarno-Ebene, Italien: Landschafts- und siedlungsarchäologische Untersuchungen - Seiler, Florian; Vogel, Sebastian; Kastenmeier, Pia (e-Forschungsberichte des DAI, 2023)
The SALVE-research project (www.salve-research.org) aims at reconstructing the cultural landscape around Pompeii, i.e. the Sarno River plain, before the AD 79 eruption of Somma-Vesuvius. Special attention is drawn on paleo-topographical and paleo-environmental conditions as well as on socio-economic interrelationships particularly related to the ancient rural settlements (villae rusticae) and agricultural land use as well as to the ancient building materials. To gain deeper insight into Roman agricultural practice a geoarchaeological excavation was carried out in direct vicinity to a villa rustica to uncover a pre-AD 79 Roman agricultural soil and conduct multi-disciplinary analyses.